Synthesis and Characterization of Cobalt(II), Nickel(II) and Copper(II) Complexes derived from Aromatic Diamines and Hetercyclic Aldehyde - Kumar, M.; Sinha, A.K. (Asian Journal of Chemistry, 2012)
Ligands derived from pyridine-2-aldehyde, o-phenylenediamine (Palophen) and m-phenylenediamine (Palmphen) have been prepared. Complexes of Cu(II), Co(II) and Ni(II) have been synthesised and characterized on the basis of elemental analysis, molar conductance, IR, UV and magnetic moment data. [Cu(Palophen)2]Cl2, [Cu(Palm-phen)2]Cl2, [Ni(Palophen)2]Cl2 and [Ni(Palmphen)2]Cl2, were diamagnetic and square-planar. However, rest of Cu(II), Ni(II) and all the Co(II) complexes showed μeff indicative of their octahedral or distorted octahedral structure.